Design Of The Tracking Complex For A Tracking Radar System - Brooker, Graham Michael (My University, 2015)
This report deals with the design of the Tracking Loop and those functions involved with it, for a ship-borne Tracking Radar System. The report begins by placing the problem in perspective from an historical point of view by surveying some of the literature available. A realistic environment in which the radar could be expected to operate is postulated in some deti.il. Following that, the actual design of a tracker to suit that environment is conducted. Simulations of proposed configurations were a major part of the design methodology, as they best indicated the performance of the loop. These were written in FORTRAN-77 on a VAX Computer and displayed using modified PLOT-IO and PI.OT-21 software packages. Since the design and simulation of the entire Tracking Radar System was not covered in this dissertation, no major conclusions could be drawn concerning the performance of the Tracking Loop in the overall Tracking Radar System. Such results will have to await a full system simulation such as that proposed later in this report.